Synthesis and Functionalization of a 1,2-Bis(trimethylsilyl)-1,2-disilacyclohexene That Can Serve as a Unit of cis-1,2-Dialkyldisilene - Naohiko Akasaka; Kaho Tanaka; Shintaro Ishida; Takeaki Iwamoto (Inorganics, 2018)
π-Electron compounds that include multiple bonds between silicon atoms have received much attention as novel functional silicon compounds. In the present paper, 1,2-bis(trimethylsilyl)-1,2-disilacyclohexene 1 was successfully synthesized as thermally stable yellow crystals. Disilene 1 was easily converted to the corresponding potassium disilenide 4, which furnished novel functionalized disilenes after the subsequent addition of an electrophile. Interestingly, two trimethylsilyl groups in 1 can be stepwise converted to anthryl groups. The novel disilenes derived from 1 were characterized by a combination of nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry (MS), elemental analyses, and X-ray single crystal diffraction analysis. The present study demonstrates that disilene 1 can serve as a unit of cis-1,2-dialkyldisilene.